Islamic Law and Digital Transformation: A Contemporary Fiqh Analysis of Ethics, Muamalah, and Artificial Intelligence - Muntazar, Nazril; Bin Soberi, Muhammad Fauzan (Institut Agama Islam Negeri Kendari, 2026)
Information technology has brought profound changes to the social, economic, and legal behavior of Muslims. This study addresses the problem of how Islamic law responds to ethical and jurisprudential challenges in the digital era, including electronic transactions, social media, data protection, privacy, and artificial intelligence (AI). The purpose of this research is to examine the response of modern fiqh to these phenomena and assess their alignment with the principles of maqāṣid al-syarī‘ah. The study employs a qualitative method through library research analyzing forty primary and secondary sources, including Scopus- and SINTA-indexed journals, DSN-MUI fatwas, and Majmaʿ al-Fiqh al-Islami reports. The data were interpreted using a descriptive-analytic method, involving reduction, categorization, and thematic synthesis. Findings indicate that Islamic law demonstrates strong adaptability through the principles of maslahah mursalah, collective ijtihad, and maqāṣid al-syarī‘ah in addressing digital transformations. In economic transactions (muamalah), fairness and transparency justify the permissibility of online trade and sharia fintech. In the sphere of social media ethics, concepts such as al-akhlaq al-karimah and tabayyun govern moral digital conduct. Regarding privacy and AI, Islamic law underscores the protection of human dignity (hurmah al-insān) and the moral accountability of technology developers. In conclusion, Islamic law is not merely reactive but provides a proactive ethical and legal framework. The study recommends establishing a Sharia-based digital ethics institution and fostering multidisciplinary collaboration among scholars, jurists, and technologists to advance the development of digital fiqh in contemporary society.